2013
DOI: 10.1055/s-0033-1347238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera Bark Extracts on Dexamethasone-induced Insulin Resistance in Rats

Abstract: The present study indicates that AE of Moringa oleifera prevents dexamethasone-induced insulin resistance in peripheral tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Third, the included studies mostly used male rodents and the outcome could be different when more studies include females or both sexes. Fourth, dexa-induced insulin-resistant rodent models were generated by injection simultaneously during dietary modulation with or without MO in two included studies; thus, there is at least a slight possibility that the investigators' technical skill for chemical injection could directly or indirectly have influenced the experimental outcome of blood glucose levels [43,54].…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Third, the included studies mostly used male rodents and the outcome could be different when more studies include females or both sexes. Fourth, dexa-induced insulin-resistant rodent models were generated by injection simultaneously during dietary modulation with or without MO in two included studies; thus, there is at least a slight possibility that the investigators' technical skill for chemical injection could directly or indirectly have influenced the experimental outcome of blood glucose levels [43,54].…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Similarly, in present research work oral administration of Me.Mo for consecutive 60 days significantly decreased HFD-induced glucose concentration, however, no marked changes were observed in the model-HFD group. The insulin-sensitizing effect of Me.MO may be due to stimulatory action on receptor insulin signaling pathways as attributed in previously published inline studies [39,40].…”
Section: Discussionmentioning
confidence: 79%
“…The progression of diabetes was significantly reduced in STZ-diabetic rats treated with methanol extract M. oleifera pods for 21 days with treated animals showing a significant reduction in serum glucose and nitric oxide, with concomitant increases in serum insulin and protein levels [130]. It has also been shown that extracts of the bark of the plant prevented dexamethasone-induced insulin resistance in peripheral tissues [131].…”
Section: Moringa Oleiferamentioning
confidence: 99%